1997
DOI: 10.1165/ajrcmb.17.1.2594
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Airway Surfactant: Surface-tension Function, Biochemical Composition, and Possible Alveolar Origin

Abstract: Alveolar surfactant is well known for its ability to reduce minimal surface tension at the alveolar air-liquid interface to values below 5 mN/m. In addition, it has been suggested that an analogous conductive airway surfactant is also present in the airways. To elucidate the composition, possible origin, and surface activity of conductive airway phospholipids (PL), we compared in adult porcine lungs the PL classes and phosphatidylcholine (PC) molecular species of nonpurified tracheal aspirate samples with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 37 publications
(42 reference statements)
8
124
1
1
Order By: Relevance
“…The presence of a linear relationship between DSP and SP-A and -B in our LAF (data not shown) strongly suggests that this method of sampling reflects surfactant composition. BERNHARD et al [19] also found that conducting airway fluid reflected alveolar surfactant composition. Numerous other investigators have used aspirated fluid to examine surfactant composition in neonates [20][21][22], children [23] and adults [24] with respiratory failure, and noted that the relative surfactant composition is similar to that obtained from BAL.…”
Section: Surfactant Samplingmentioning
confidence: 94%
“…The presence of a linear relationship between DSP and SP-A and -B in our LAF (data not shown) strongly suggests that this method of sampling reflects surfactant composition. BERNHARD et al [19] also found that conducting airway fluid reflected alveolar surfactant composition. Numerous other investigators have used aspirated fluid to examine surfactant composition in neonates [20][21][22], children [23] and adults [24] with respiratory failure, and noted that the relative surfactant composition is similar to that obtained from BAL.…”
Section: Surfactant Samplingmentioning
confidence: 94%
“…Although the major physiologic function of pulmonary surfactant is to confer mechanical stability to the alveoli and the small airways (22)(23)(24), there is growing evidence that pulmonary surfactant also has a potential role in modulating infl ammation in normal and injured lungs (25)(26)(27)(28)(29)(30). Our previous work ( 31,32 ) and that of others (33)(34)(35)(36) have shown that surfactant lipids modulate the release of oxidative and infl ammatory mediators from infl ammatory cells.…”
Section: Lps Binding Assaymentioning
confidence: 99%
“…Because Clara cells from the conductive airways are able to synthesize SPs (21,22), further studies will be needed to ascertain differences between surfactant samples from TA and alveolar surfactant. Several investigators found similar surfactant composition in TA and bronchoalveolar lavage fluid (23,24), but SP-A, SP-B, and SP-C were found to be lower in TA than in lung lavage fluid (23). Of note, surfactant analysis from TA is currently the standard method for the study on surfactant in human research (3).…”
Section: General Considerationsmentioning
confidence: 99%